From media-party linkages to ownership concentration causes of cross-national variation in media outlets' economic positioning - Erik Neimanns; Nils Blossey (Max Planck Institute for the Study of Societies, 2022)
A sizable literature on media bias suggests that media coverage is frequently biased towards certain political and economic positions. However, we know little about what drives variation in political and ideological bias in news coverage across countries. In this paper, we argue that increasingly commercialized and concentrated media markets are likely to be associated with media coverage leaning more favorably towards economically more right-wing positions. Media bias should reflect the preferences of media owners and should be a result of a reduced diversity of news media content. In contrast, where media outlets continue to be oriented more closely along partisan lines, often referred to as political parallelism, bias on economic issues should be more likely to cancel out at the aggregate level. To test these claims, we combine expert survey data on partisan attachments of media outlets, party ideologies, and media ownership concentration for twenty-four European countries. Results from multilevel regression models support our theoretical expectations. With media framing potentially affecting individual-level preferences and perceptions, high and rising levels of media ownership concentration may help to explain why governments in the affluent Western democracies often do remarkably little to counter trends of rising income inequality. – – Zahlreiche Untersuchungen zu Medienberichterstattung legen nahe, dass Medien in ihrer Berichterstattung oftmals bestimmte politische und wirtschaftliche Positionen unterstützen. Bislang gibt es allerdings kaum Befunde dazu, warum diese Positionierungen über Länder variieren können. In diesem Beitrag argumentieren wir, dass zunehmend konzentrierte Medienmärkten dazu beitragen, dass Medien stärker wirtschaftsliberale Positionen befürworten. Gründe hierfür können in den Positionen der Eigentümer in Kombination mit einer gesunkenen Vielfalt der Berichterstattung liegen. Richten sich Medien dagegen weiterhin enger an politischen Parteien aus, oftmals als politischer Parallelismus bezeichnet, sollten sich Verzerrungen in der Berichterstattung zu ökonomischen Themen in der Summe eher ausgleichen. Um unsere Erwartungen zu testen, analysieren wir Daten aus Expertenumfragen für vierundzwanzig europäische Länder zu parteipolitischer Ausrichtung von Medien, Parteipositionen und Eigentümerkonzentration. Die Ergebnisse von Mehrebenenregressionsmodellen stützen unsere theoretischen Erwartungen. Über die Medienberichterstattung vermittelte Framingeffekte haben ein großes Potenzial, individuelle Wahrnehmung und Präferenzen zu beeinflussen. Eine hohe und steigende Medieneigentümerkonzentration kann entsprechend helfen zu erklären, warum Regierungen in den wohlhabenden westlichen Demokratien oftmals nicht mehr tun, um einer steigenden Einkommensungleichheit zu begegnen.
hdl:21.11116/0000-000B-7A8A-1
Keywords: 300; media bias; media framing; media ownership concentration; political parallelism; Medienbias; Medieneigentümerkonzentration; Medienframing; politischer Parallelismus